2015
DOI: 10.1080/15548627.2015.1037061
|View full text |Cite
|
Sign up to set email alerts
|

SYK regulates macrophage MHC-II expression via activation of autophagy in response to oxidized LDL

Abstract: I Miller (2015) SYK regulates macrophage MHC-II expression via activation of autophagy in response to oxidized LDL, Autophagy, 11:5,[785][786][787][788][789][790][791][792][793][794][795]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 47 publications
5
39
0
Order By: Relevance
“…However, the mechanism of ox-LDL in autophagy regulation remains controversial. Some studies indicate that ox-LDL induces autophagosome and autolysosome formation by upregulating expression of OLR1 47,48 or peroxisome proliferator-activated receptor gamma (PPARG) 49 and their downstream production of reactive oxygen species (ROS). Excessive generated ROS in response to damaged mitochondria which escape from autophagy, causes cellular dysfunction and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of ox-LDL in autophagy regulation remains controversial. Some studies indicate that ox-LDL induces autophagosome and autolysosome formation by upregulating expression of OLR1 47,48 or peroxisome proliferator-activated receptor gamma (PPARG) 49 and their downstream production of reactive oxygen species (ROS). Excessive generated ROS in response to damaged mitochondria which escape from autophagy, causes cellular dysfunction and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…CyPA can be secreted from RASMC in response to the ROS inducer LY83583 [11,12]. ox-LDL, as a proatherogenic factor, induces intracellular production of ROS in various cell types such as VSMC [8,9,10] and macrophages [26,27,28]. It has been reported that ox-LDL induces CyPA secretion from THP-1 via an unknown mechanism [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Abcg1 −/− macrophages have been shown to display enhanced proinflammatory cytokine production (117, 118). OxLDL induces autophagosome formation, MHC-II expression, and phosphorylation of SYK in macrophages (119). Several studies have suggested a role for cholesterol in the development and maturation of dendritic cells.…”
Section: Effects Of Cholesterol On Antigen Presenting Cellsmentioning
confidence: 99%